Scholarship Planners Tour Academy - Laird, Robert (Venice, CA Evening Vanguard, Venice)
The T. S. Golden Bear, training ship for California Maritime Academy students, was visited by leaders of Culver City who are working toward a scholarship program for local students. The program would be aimed at youths who are interested tn attending colleges like the Maritime Academy or similar California schools.